The Multiplicity of Muhammadiyah’s Political Engagement in Indonesia’s DPD Election - Wardana, Amika; Hidayat, Syahrul (Studia Islamika, 2019)
The establishment of the DPD (Dewan Perwakilan Rakyat or Regional Representative Council) in Indonesia in 2004 has provided individuals and civil society organizations such as Muhammadiyah with the opportunity to participate in the legislative process without formally entering politics. As exemplified by three cases in Yogyakarta, South Sulawesi and West Sumatra, three local Muhammadiyah branches have participated in the last three DPD elections (2004, 2009, and 2014), with each winning a seat each in the 2014 election. This reveals the inherently political nature of civil-cum-Islamic social-religious organizations such as Muhammadiyah, which will manifest itself whenever opportunities become available. Yet, due to different organizational strengths and the social-cultural capital of each local branch office, diverse approaches and political strategies were used to mobilize members and sympathizers, thereby encouraging them to vote.